LANGUAGE CHANGE AND EVOLUTION: THE HISTORICAL DEVELOPMENT AND MODERN TRANSFORMATIONS OF THE ENGLISH LANGUAGE (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
This thesis investigates the historical development and modern transformations of the English language, exploring how it has evolved from its early forms to its contemporary usage. By examining the major phases of English language development, including Old English, Middle English, and Early Modern English, as well as recent linguistic changes, this study aims to provide a comprehensive understanding of the processes driving language change and the factors influencing its evolution in the modern era.